An extended stable isotope‐labeled signature peptide internal standard for tracking immunocapture of human plasma osteopontin for LC‐MS/MS quantification. (27th April 2015) - Faria, Morse; Halquist, Matthew S.; Yuan, Moucun; Mylott, William; Jenkins, Rand G.; Karnes, H. Thomas
Abstract A stable isotope‐labeled signature peptide, whose sequence corresponds to the human osteopontin (hOPN) specific antibody epitope, was evaluated as an internal standard to compensate for immunocapture variability during quantification of hOPN by immunoaffinity‐coupled LC‐MS/MS. Immunocapture variability was induced by varying the antibody amount per well from 150 to 4500 ng and analysis was carried out with internal standards added before and after the immunocapture step. The immunocapture variability ranged from −80.9 to 77.0% when the IS was added after immunocapture and from −37.5 to 20.3% when the internal standard was added before immunocapture. The lower variability demonstrates the ability of stable labeled isotope internal standard peptide to compensate for variation during immunocapture. Copyright © 2015 John Wiley & Sons, Ltd.